α-Amylase and α-glucosidase inhibitory activities of the extracts and constituents of Ferulago blancheana, F. pachyloba and F. trachycarpa roots - Karakaya, Songül; Özbek, Hilal; Gözcü, Sefa; Güvenalp, Zühal; Yuca, Hafize; Duman, Hayri; Kazaz, Cavit; Kiliç, Ceyda Sibel (Bangladesh Journal of Pharmacology, 2018)
Eleven coumarins named osthole (1), imperatorin (2), bergapten (3), prantschimgin (4), grandivitinol (5), suberosin (6), xanthotoxin (7), felamidin (8), marmesin (9), umbelliferone (10), ulopterol (11), and a sterol mixture consisted of stigmasterol (12), β-sitosterol (13) were isolated from the roots of Ferulago blancheana, F. pachyloba and F. trachycarpa through in vitro bioassay-guided fractionation processes. The extracts and bioactive compounds were evaluated for their α-amylase and α-glucosidase activities. Among the tested compounds, felamidin and suberosin showed significant α-glucosidase inhibitory activity with IC50 values of 0.4 and 0.9 mg/mL, respectively, when compared to the reference standard acarbose (IC50 = 4.9 mg/mL). Grandivitinol (IC50 = 20.0 mg/mL) had the lowest inhibitory effect. On the other hand, none of the tested extracts were found to be active on α-amylase inhibition. This is the first report on isolation, characterization of the bioactive compounds and evaluation the α-amylase and α-glucosidase inhibitory activities of these species. Video Clip of Methodology: 8 min 26 sec: Click to watch